Soetomo Score as a Predictor of HIV-Associated Neurocognitive Disorders - Fajar Rudy Qimindra (Hampstead Psychological Associates, 2020)
Background HIV-Associated Neurocognitive Disorders (HAND)wasone of theneurological complicationsof HIVinfection. However, there were no biomarkers have been sufficiently validated for prognosis HAND. Objective: To develop a scoring system and determine prognostic values of Soetomo Score as Predictor of HIV-Associated Neurocognitive Disorders (SSP HAND). Methods: The case-control study was performed at the UPIPI out-patient clinic. The examination is performed using MoCa-Ina.Eight parameters which were possible to be a predictor of HAND were analyzed by bivariate and multivariate. Results were analyzed using calibration test and discrimination test produced Area Under Curve (AUC) value. The cut-off point could make identification of good and bad prognostics. Results: The equation of SSP HAND was Y=-4.164+1.249 score total of SSP HAND. AUC value of this score was 80.9% (95% CI=71.1%-90.6%). The value of SSP HAND was ≥3.5,it means that the sensitivity was74,4% and the specificity was79.5%. Subject with score 0–3 had good prognostic while score 4–5 had bad prognostic. Conclusion: Value of SSP HAND ≥3.5 could make a good prediction of HAND.